Quercetin: A Phytochemical with Pro-Apoptotic Effects in Colon Cancer Cells - Ozsoy, Serpil; Soykut, Gunsu; Becer, Eda (Galenos Publ House, 2022)
The anti-carcinogenic effects of polyphenols have been demonstrated over the years. Polyphenols can show anti-carcinogenic effects by providing signal transduction related to cancerous cell growth, suppression of oncogene expression, arachidonic acid metabolism, inhibition of pro-inflammatory pathways, triggering apoptotic cell death, and inhibition of angiogenesis. The capacity of phenolic compounds due to their effects on many signaling pathways in cells might indicate the potential use of polyphenols as anti-carcinogenic agents. An important and well-studied polyphenol, quercetin, has been shown to have anti-inflammatory and anti-carcinogenic effects. Apoptosis is activated by many intracellular and extracellular signals through two main signaling pathways; the extrinsic pathway and the intrinsic pathway, and regulated by many proteins. In addition to the anti-inflammatory effect of quercetin, its anti-carcinogenic effect is a topic of interest. Quercetin has the potential to induce apoptosis via the mitochondrial apoptotic pathway by causing changes in the mitochondrial membrane potential. In addition, quercetin also induces apoptosis through the activation of p53, increasing the expression of pro-apoptotic molecules such as Bax, caspase-3, caspase-9, and inhibition of anti-apoptotic proteins such as Bcl-2. In conclusion, given the pro-apoptotic and anti-cancer effects of quercetin, its potential for use as a component of cancer therapy might be suggested as an alternative to other colon cancer treatments.
Keywords: Quercetin; colon cancer; polyphenols; apoptosis; anti-carcinogenic; cell death